Professional Identity Emergence in a New Profession - Panda, Madhu Chhanda; Kar, Brajaballav (Prabandhan: Indian Journal of Management, 2024)
Purpose : The field of HIV/AIDS counseling plays a vital role in the fight against the illness. The field is new, lacking public health and other health specialists, and is less integrated with the larger health system. This environment will probably have a negative impact on the development of the professional identity (PI). In this study, the evolution of PI was examined. Strong PI is necessary for the survival and expansion of the numerous new professions that are constantly emerging. Design/Methodology/Approach : A semi-structured interview was appropriate to explore the emerging profession and its PI development process. In-depth interviews of six experienced HIV/AIDS counselors in Odisha were conducted. Interviews captured counselors’ lived experiences, challenges, and expectations. The analysis of the transcripts involved finding recurring themes and assigning causality to the PI. Findings : Early adopters and pioneers must overcome initial obstacles, establish policies, prove their knowledge, redefine professional limits, and promote the area and its PI in order to be recognized professionally and by the public. Evangelists back the newly formed field, leading to iterative improvements in its structure, processes, and roles, thereby shaping a distinct identity for practitioners. Their educational background and moral character influenced a candidate’s career. Their role within the company, the organizational structure, the benefits offered, the availability of resources, acceptability, and recognition all affect how they perceive their impact. Originality : A process view of PI development was identified for an emerging profession. Research Limitations : There was no outsider’s perspective on the field because the sample size was restricted to seasoned professionals exclusively. Practical Implications : The model developed in this study is helpful for understanding how PI emerges, enhancing the profession’s effectiveness, and lowering barriers to its development. Social Implications : Professions with a stronger PI tend to be more effective in service delivery.